Teaching and learning strategies foe English language speaking skill among early childhood education (ECE) undergraduates - Hasviniy Padmanathan (2021)
This study aimed to develop a provisional framework of English language speaking skills for early childhood education (ECE) undergraduates. This study was carried out to identify the level of speaking proficiency among the undergraduates, ascertain the challenges faced by them in using English, and determine teaching and learning strategies to overcome the challenges. The study adopts the mixed-method approach. The method used for quantitative data was a survey and speaking test from 90 respondents. The method used for qualitative data was document analysis of 90 language test scores and semi-structured interviews with three students from each semester and five ECE lecturers. The English proficiency level was acquired through the respondents speaking test scores. The online survey was conducted to ascertain the challenges faced by undergraduates. The semi-structured interviews of students and lecturers were conducted to determine teaching and learning strategies towards overcoming those challenges. The survey was analysed using descriptive analysis of the statistical data. Thematic analysis was used to analyse the interview data. The findings revealed that there were no significant differences in speaking proficiency levels between respondents from different semesters (p value=.400). This suggested that there had been no significant improvement in their speaking proficiency level as they progress in their semesters. The findings on the challenges were fear of criticism, limited vocabulary, shyness and no motivation. The findings on the strategies were communication-based language learning techniques, constant use of English and positive language exploration. In conclusion, the provisional Framework of English Language Speaking Skills was developed based on the challenges faced by ECE undergraduates and the strategies employed by them to overcome those challenges. The implication of this study suggests that the framework provides a vital reference for future researchers on how to improve ECE undergraduates English speaking skills.